PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 1 PEKANBARU - Abdul Mukti; Jesi Alexander Alim; Neni Hermita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRAKThe mathematics result of fourth grade students of SD Negeri 1 Pekanbaru are too low because students were subjects who geint knowledge so that they were pasive learning process. 13 out of 32 students, 40,62%, reached KKM. The purpose of this study is to Improve Student Mathematics Learning Outcomes throught implementation of direct Learning Model. The research problem is wether implementation direct of can improve mathematics out comes of fourth grade students of SD Negeri 1 Pekanbaru? Based on the research the results of the study indicated that teacher is activities increased about 15% from 77,5% in the first cycle with a good category to 92,5% in the second cycle with a very good category. Students activites also increased about 10% from 82,5% in the first cycle to 92,5% in the second cycle with a very good category. Learning outcomes of students increased 14,31 from a base score with an average 61,56 to 75,87 in UH of first cycle and increased 22,5 to 84,06 at UH of second cycle. Classical completness also increased 25% from 40,62% to 65,62% in the first cycle. Then it increased 25% to 90,62% in the second cycle. Based on thing research it can be concluded that the implementation of Direct Learning Model can improve mathematics learning outcomes of fourth grade students of SD Negeri 1 Pekanbaru.Keywords : Model , Direct Learning , Math Learning Outcomes